Implikasi Indikator Keuangan Terhadap Tax Avoidance - Maya Novitasari; Siti Suharni (AFRE (Accounting and Financial Review), 2019)
This study aims to determine the effect of fixed asset intensity, inventory intensity, advertising, debt, profitability and firm size on tax avoidance. Tax avoidance is proxied into cash ETR (Effective Tax Rate). The sampling technique used was purposive sampling. Data is obtained from secondary data from annual reports of the consumer goods industry sector listed on the Indonesia Stock Exchange from 2013 to 2016. The amount of data obtained is 32 data. Data analysis is done by multiple linear regression. The results of this study are the intensity of fixed assets, the intensity of supply, advertising, debt, profitability, and firm size simultaneously have a significant effect on tax avoidance. Partial Test shows that inventory intensity affects tax avoidance in a positive direction. While the intensity of fixed assets, advertising, debt, profitability and company size does not affect tax avoidance. DOI: https://doi.org/10.26905/afr.v2i1.3177